Students perceptions toward using classroom debate to develop critical thinking and oral communication ability - Zare, Pezhman; Othman, Moomala (Canadian Center of Science and Education, 2015)
The purpose of this study was to make inquiries about students’ perceptions on employing classroom debate toimprove critical thinking and oral communication ability. Sixteen undergraduate students were randomlyassigned to a group, and took part in debates for nine sessions throughout one whole semester. Part of the datawas collected through a survey questionnaire including twenty one statements using 5-point Likert scale.Students were also provided with a number of open-ended questions to write down their perceptions about theclassroom debate. In addition, semi-structured interviews were conducted with a number of volunteeredparticipants. Overall, the students believed that the classroom debate was a constructive learning activity. Therespondents believed that the debates helped improve their critical thinking skills and oral communication ability.In addition, as the students claimed, other benefits of the debates included mastering the course content, boostingconfidence, overcoming the stage fright, and improving team work skills.